The Relationship Between Burnout, Depression, and Anxiety: A Systematic Review and Meta-Analysis - Koutsimani, Panagiota; Montgomery, Anthony; Georganta, Katerina (Frontiers in Psychology, 2019)
Background: Burnout is a psychological syndrome characterized by emotional exhaustion, feelings of cynicism and reduced personal accomplishment. In the past years there has been disagreement on whether burnout and depression are the same or different constructs, as they appear to share some common features (e.g. loss of interest and impaired concentration). However, the results so far are inconclusive and researchers disagree with regard to the degree to which we should expect such overlap. The aim of this systematic review and meta-analysis is to examine the relationship between burnout and depression. Additionally, given that burnout is the result of chronic stress and that working environments can often trigger anxious reactions, we also investigated the relationship between burnout and anxiety. Method: We searched the online databases SCOPUS, Web of Science, MEDLINE (PubMed) and Google Scholar for studies examining the relationship between burnout and depression and burnout and anxiety, which were published between January 2007 and August 2018. Inclusion criteria were used for all studies and included all types of studies (cross-sectional and longitudinal), published and unpublished research articles, full-text articles, articles written in the English language, studies that present the effects sizes of their findings and that used reliable research tools. Results: Our results showed a significant association between burnout and depression (r = 0.520, SE = 0.012, 95% CI = 0.492, 0.547) and burnout and anxiety (r = 0.460, SE = 0.014, 95% CI = 0.421, 0.497). However, moderation analysis for both burnout - depression and burnout - anxiety relationships revealed that the studies in which the MBI test was used and were rated as having poorer quality showed lower effect sizes. Conclusions: Our research aims to clarify the relationship between burnout - depression and burnout - anxiety relationships. Our findings revealed no conclusive overlap between burnout and depression and burnout and anxiety, indicating that they are different and robust constructs. Future studies should focus on utilizing more longitudinal designs in order to assess the causal relationships between these variables.